Tennyson's Maud : The Biographical Genesis. - Rader, Ralph Wilson (Berkeley : University of California Press, 2022)
""This book was born out of the curiosity aroused in me by Tennyson's Maud and ""Locksley Hall,"" ostensibly dramatic poems which were strangely flawed, I always felt, by some hidden emotional connection with the poet's own life. What was it? . . . The final result of my inquiry is this book."" --From the Preface by the Author This title is part of UC Press's Voices Revived program, which commemorates University of California Press's mission to seek out and c.
Description based upon print version of record.
JSTOR
Keywords: Tennyson, Alfred Tennyson, -- Baron, -- 1809-1892.; English poetry -- 19th century